Integration of Information Technology into Educational Assessment Systems Through Digital Report Cards - Eka Maftuhatil Riskiyah; Revi Rusdatul Jannah; Zainal Arifin Ahmad (Journal of Educational Sciences, 2026)
The integration of information technology in the education system has become an urgent need, especially in the academic assessment system. One of the growing innovations is the implementation of digital report cards as a replacement for conventional assessment systems. This study aims to analyze the readiness of educators in adopting this technology, identify the benefits and challenges in its implementation, and provide strategic recommendations to optimize the implementation of digital report cards. Using a descriptive qualitative approach, data were collected through a questionnaire with narrative answers and a review of relevant literature. The results showed that digital report cards provide significant benefits in improving the efficiency, transparency, and accuracy of the assessment system. However, some challenges are still faced, such as limited infrastructure, low digital literacy of educators. Therefore, the strategic recommendations include improving technology infrastructure and continuous training for educators. With the right strategy, digital report cards can be an innovative solution in the education system, support broader digital transformation, and improve the quality of academic management in educational institutions.